Clozapine and cardiotoxicity – A guide for psychiatrists written by cardiologists. (December 2019) - Patel, Rishi K.; Moore, Alice M.; Piper, Susan; Sweeney, Mark; Whiskey, Eromona; Cole, Graham; Shergill, Sukhi S.; Plymen, Carla M.
Highlights: Cardiovascular side-effects of clozapine are rare but include life-threatening myocarditis and dilated cardiomyopathy, but there is no clear evidence that the dose of clozapine has a direct effect on the risk of cardio-toxicity. Clozapine-induced cardiotoxicity is likely over-reported in the literature with few patients receiving appropriate cardiac investigations. Only one protocol for monitoring of clozapine-induced cardiotoxicity exists which recommend baseline troponin, C-reactive protein and transthoracic echocardiogram. Abstract: This review discusses the rare but potentially life-threatening cardiovascular side-effects of myocarditis and dilated cardiomyopathy associated with the use of Clozapine. The clinical presentation of these conditions is non-specific, making it difficult to both risk-stratify and identify patients who develop these consequences. This review aims to examine the proposed aetiologies, diagnostic approaches and subsequent management strategies of cardiotoxicity associated with clozapine use; offering guidance to psychiatrists and general physicians. Current evidence highlights the importance of accurate diagnosis to prevent premature and unnecessary cessation of clozapine. Guidance on monitoring and reintroduction of the drug is emerging and current practice recommends a combination of regular monitoring of biomarkers and imaging to make a diagnosis of cardiotoxicity although further work is needed to establish evidence-based guidelines.